Improving Student Learning Outcomes in Martial Arts Materials through Learning Videos in Grade IX at Smpn 2 Banjarbaru - Zuhdi, Dandi Hammam; Anggara, Norma; Arifin, Syamsul (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The purpose of this study is to find out if there is an increase in student learning outcomes in Pencak Silat martial arts materials through learning videos in grade IX at SMPN 2 Banjarbaru. The research uses qualitative methods which apply logical statistical systems, ethics, nonparameters and aesthetics. Data collection techniques are carried out by observation, interviews, and knowledge tests. The sample in this study is students of class IX G of SMPN 2 Banjarbaru, consisting of 34 participants. Based on the results of the research on improving student learning outcomes in pencak silat martial arts materials through learning videos in grade IX at SMPN 2 Banjarbaru, in the initial test of doing knowledge questions, it was seen that students got an average score of 56 which was still far below the KKM. However, after watching the learning video made by the researcher and then working on the knowledge questions, the average result of the student's scores increased to 85. Conclusion of students' learning outcomes on pencak silat martial arts material through learning videos in grade IX at SMPN 2 Banjarbaru is effective in improving learning outcomes and increasing their interest and motivation in learning.